Poverty by Design: The Role of Charity and the Cultivated Ethical Citizen. Issue 4 (14th October 2022) - Parsell, Cameron; Clarke, Andrew; Perales, Francisco
Abstract : Across numerous countries with advanced welfare states, governments have relied on a hybrid of publicly funded and delivered welfare services and voluntary charity to meet the needs of people in poverty. Driven by austerity and economic downturns, many scholars agree that governments are increasingly relying on charity as a response to poverty. Taking Australia as a case study, this article demonstrates how the decayed welfare state is not just about outsourcing welfare provision to charities, but also a part of a broader project to cultivate a society in which social problems are responded to through spontaneous, community-led initiatives, powered by the ethical commitment of everyday citizens. We show how this project produces poverty through welfare state retrenchment, whilst simultaneously cultivating charity through material and symbolic support from the state. This results in the construction of charity as an end in itself, with little consideration given to its effectiveness in alleviating poverty.